Single-nucleotide polymorphism (SNP) genotyping assays for the varietal authentication of 'Nebbiolo' musts and wines. (15th May 2020) - Boccacci, Paolo; Chitarra, Walter; Schneider, Anna; Rolle, Luca; Gambino, Giorgio
Highlights: 'Nebbiolo'-specific single-nucleotide polymorphisms (SNPs) were identified. SNP TaqMan® genotyping assays detected 'Nebbiolo' genotype in all wine-making steps. SNP genotyping assays identified must mixtures at 1% and wine mixtures at 10–20%. In commercial wines, low-quality DNA limited the efficiency of the SNP assays. SNPs are promising and user-friendly markers for varietal identification in wine. Abstract: 'Nebbiolo' ( Vitis vinifera L.) is renowned for its use in producing monovarietal high-quality red wines, such Barolo and Barbaresco. The fight against fraud to safeguard high-quality productions requires an effective varietal identification system applicable in musts and wines. 'Nebbiolo'-specific single-nucleotide polymorphisms (SNPs) were identified starting from available databases and 260 genotypes analysed by Vitis18kSNP array. Two SNPs were sufficient to identify 'Nebbiolo' from 1157 genotypes. The SNP TaqMan® genotyping assays developed in this work successfully identified 'Nebbiolo' in all musts and wines collected at different experimental wine-making steps. The high sensitivity of the assays allowed identification of must mixtures at 1% and wine mixtures at 10–20% with non-'Nebbiolo' genotypes. In commercial wines, the amplification efficiency was limited by the low amount of grapevine DNA and the presence of PCR inhibitors. The TaqMan® genotyping assay is a rapid, highly sensitive and specific methodology with remarkable potential for varietal identification in wines.